Leadership and Emotional Intelligence: Current Trends in Public Health Professionals Training - Reshetnikov, Vladimir A.; Tvorogova, Nadezhda D.; Hersonskiy, Ilya I.; Sokolov, Nikita A.; Petrunin, Alexander D.; Drobyshev, Dmitriy A. (Frontiers in Public Health, 2020)
Aim of the Study: The objective of this study was to identify and compare the most significant personal features, and social and psychophysiological characteristics of future health-care managers in order to improve the training program for specialists in the field of health care and public health on the basis of modern concepts about the necessary leadership skills and competence. Significance: The results of the study make it possible to evaluate the effectiveness of career guidance and selection for training future health-care managers on the basis of the application of the following methods: assessing emotional intelligence and taking into account the psychological characteristics of students. Materials and Methods: A total of 242 students of medical and preventive care, residents, and undergraduate students who were trained in the program “Factory of Health Leaders” were included in the study evaluating the level of professional training and indicators of emotional intelligence. Participants underwent testing using a methodology of the management style assessment, as well as testing of their psychophysiological and emotional characteristics. Results: Students who studied in the “Factory of Health Leaders” program had better indicators of emotional intelligence than had ordinary students, but their rates are comparable with residents' rates. This makes us understand that the additional training of emotional intelligence in the process of studying under the higher education program can be successful along with great practical experience in health care as part of residents' curriculum. Conclusion: The training of leadership qualities and emotional intelligence in students by using the example of comparing students in the “Factory of Health Leaders” program with students who have not undergone such training has confirmed its high efficiency and significance in the training of highly qualified personnel in health care.